Quaternary range-shift history of Japanese wingnut (Pterocarya rhoifolia) in the Japanese Archipelago evidenced from chloroplast DNA and ecological niche modeling. Issue 5 (3rd September 2017) - Sugahara, Kanako; Kaneko, Yuko; Sakaguchi, Shota; Ito, Satoshi; Yamanaka, Keisuke; Sakio, Hitoshi; Hoshizaki, Kazuhiko; Suzuki, Wajirou; Yamanaka, Norikazu; Isagi, Yuji; Momohara, Arata; Setoguchi, Hiroaki
ABSTRACT: Based on organelle DNA phylogeographic analyses and ecological niche modeling (ENM), we investigated the range-shift history of the Japanese wingnut ( Pterocarya rhoifolia ) during the Quaternary climatic oscillations with particular emphasis on the Last Glacial Maximum (LGM). Phylogeographic patterns of this species were determined using 376 individuals from 53 populations for chloroplast DNA sequencing of three spacers. Spatial analysis of molecular variance revealed that the current phylogeographic structure would be sculptured by multiple range shifts from each glacial refugium, which would have been repeated several times during the Quaternary climatic oscillations. High haplotype diversity and private haplotypes were detected in southwestern Japan, where wingnut is currently infrequent and found mainly in high mountains, whereas in northernmost Japan, haplotype diversity was low though this plant is quite common at present. According to ENM approach, during the LGM, the climatically suitable distribution areas were not recovered in northeastern Japan but in lowlands of southwestern Japan. Our combined results suggest that Japanese wingnut primarily persisted in the lowlands of southwestern Japan and coastlines below 36.5°N latitude during the LGM, having led to the postglacial range expansion from the refugia in each area of southwestern and lower latitudinal northeastern Japan, and to the wide-range recolonization from the southerly refugium/refugia to the north in northernmost Japan. The southwestern and coastal refugia have played a role in shaping the current haplotype diversity and phylogeographic structure, whereas some rear edge populations, harboring unique haplotypes, have been also maintained.